2000
DOI: 10.1093/ortho/27.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Signs and Symptoms of Temporomandibular Disorders in Young Nigerian Adults

Abstract: The objective of this study was to determine the prevalence of signs and symptoms of TMD in young Nigerian adults and to establish a baseline for comparison with other studies. It consisted of a cross-sectional study at Obafemi Awolowo University, Ile-Ife, Nigeria in 1997. The subjects consisted of 308 medical and dental students (207 males and 101 females) randomly selected from a Nigerian University. Their ages ranged from 17 to 32 years with a mean age of 23 +/- 3.0 years. They were assessed according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
2
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 17 publications
6
28
2
14
Order By: Relevance
“…Cinsiyetlere göre TMD görülme oranları karşılaştırıldığında ise kız öğrencilerde (%58,13) herhangi bir düzeyde TMD görülme oranının erkek öğrencilere (%21,51) göre istatistiksel olarak anlamlı derecede daha fazla olduğu tespit edilmiştir. Bazı çalışmalarda kızlarda TMD prevalansının daha yüksek olmasının; genetik yapı, mental stres, fizyolojik farklılıklardan kaynaklanabileceği bildirilmiştir (1,17,18 Literatürde, parafonksiyonel alışkanlıkların, gece ve gün-düz diş sıkma ve gıcırdatmanın ağrılı TME rahatsızlıkları ile ilişkili olduğu bildirilmiştir (19). Gece ve gündüz diş sıkma ile parafonksiyonel alışkanlıkların temel sebebinin mental stres olduğu bildirilmiştir (20,21).…”
Section: Discussionunclassified
“…Cinsiyetlere göre TMD görülme oranları karşılaştırıldığında ise kız öğrencilerde (%58,13) herhangi bir düzeyde TMD görülme oranının erkek öğrencilere (%21,51) göre istatistiksel olarak anlamlı derecede daha fazla olduğu tespit edilmiştir. Bazı çalışmalarda kızlarda TMD prevalansının daha yüksek olmasının; genetik yapı, mental stres, fizyolojik farklılıklardan kaynaklanabileceği bildirilmiştir (1,17,18 Literatürde, parafonksiyonel alışkanlıkların, gece ve gün-düz diş sıkma ve gıcırdatmanın ağrılı TME rahatsızlıkları ile ilişkili olduğu bildirilmiştir (19). Gece ve gündüz diş sıkma ile parafonksiyonel alışkanlıkların temel sebebinin mental stres olduğu bildirilmiştir (20,21).…”
Section: Discussionunclassified
“…Also, compared to healthy subjects, subjects with CMD show extremely high prevalence of various orofacial manifestations, such as xerostomia, glosodinia, dysphagia and dysgeusia 23 . Further, the results of numerous epidemiological studies have shown a significant presence of occlusal disharmony in patients with evident signs and symptoms of CMD's [24][25][26] . According to Olson (1998), etiological connection between occlusal factors and CMD must be seen in the ligh Diskusije o ovim pitanjima su i dalje aktuelne u stručnoj literaturi.…”
Section: Discusionmentioning
confidence: 99%
“…[6,7] Istraživanja sprovedena u drugim regionima sveta ukazuju na nešto manju učestalost TMP. [8,9] Epidemiološka studija na 284 pitomaca vojne akademije u Srbiji utvrdila je da učestalost TMP iznosi 70%. Najučestaliji znaci i simptomi bili su: poremećena pokretljivost donje vilice (78,5%), zvučni signali u viličnim zglobovima (20,7%), palpatorna osetljivost viličnih zglobova (2,11%) i palpatorna osetljivost mastikatornih mišića (7,4%).…”
Section: Uvodunclassified
“…[8,14] Otuyemi i sar.su istraživa-njem na Nigerijskoj populaciji utvrdili da 46% ispitanika sa TMP ima blage simptome, da 16,5% ima izražene simptome, a da samo 0,3% ispitanika ima najizraženije simptome. [9] Magnusson i sar. su utvrdili da su progresivan bol i izraziti TMP retki nalazi, kao i da se simptomiporemećaja menjaju tokom života.…”
Section: Stručni Radoviunclassified